Legal Mediators: British consuls in Tengyue (western Yunnan) and the Burma-China frontier region, 1899–1931 - WHEWELL, EMILY (Modern Asian studies, 2020)
British consuls were key agents for the British imperial presence in China from 1842 to 1943. Their role, which was to perform administrative duties that protected the rights of British subjects, is most prominently remembered in connection with the east coast. Here larger foreign communities and international maritime trade necessitated their presence. However, British consuls were also posted to the far southwest province of Yunnan and the Burma-China frontier region. This article sheds light on the role of consuls working in the little-known British consular station of Tengyue, situated close to the Burma-China frontier. Using the reports of locally stationed consuls and Burmese frontier officials, it argues that consuls were important mediators of legal power operating at the fringes of empire for British imperial and colonial interests in this region. They represented British and European subjects, and were mediators in legal disputes between British Burma and China, helping to smooth over Sino-British relations and promoting British Burmese sovereign interests. The article serves to shift our attention from the British presence in China on the east coast to the southwestern frontier, demonstrate the importance of consular legal duties, and emphasize the trans-imperial nature of British legal roles across this region.